2013
DOI: 10.1161/atvbaha.113.301931
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibits Cellular Senescence to Restore the Therapeutic Potential of Old Human Endothelial Progenitor Cells via the Hypoxia-Inducible Factor-1α–TWIST-p21 Axis

Abstract: Objective— Endothelial progenitor cells (EPCs) can significantly improve tissue repair by providing regeneration potential within injured cardiovascular tissue; however, it is challenging to obtain a sufficient amount of functional EPCs from aged patients for autologous stem cell therapy. To overcome this issue, we aimed to establish adequate ex vivo expansion protocols and identify repair modulators of cellular senescence. The senescence repair circuit of hypoxia-preconditioned senescent EPCs (hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…During hypoxia, EPCs are mobilized from the bone marrow into the peripheral blood and subsequently migrate to hypoxic tissues (2). Furthermore, hypoxia inhibits cellular senescence to restore the therapeutic potential of EPCs from elderly individuals (3). Therefore, EPCs may be developed as a promising novel treatment for ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…During hypoxia, EPCs are mobilized from the bone marrow into the peripheral blood and subsequently migrate to hypoxic tissues (2). Furthermore, hypoxia inhibits cellular senescence to restore the therapeutic potential of EPCs from elderly individuals (3). Therefore, EPCs may be developed as a promising novel treatment for ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, hypoxia notably enhanced the proliferation of EPCs. Lee et al reported that hypoxia inhibits senescence of EPCs in aged humans (15). In addition, hypoxia/ischemia triggers EPCs to proceed from bone marrow into the peripheral blood, and EPCs can differentiate into ECs following migration into the site of hypoxia/ischemia in tissues (16).…”
Section: Discussionmentioning
confidence: 99%
“…TWIST1 cooperates with K-Ras G12D in lung tumorigenesis through suppressing key drivers of cell senescence such as p21 Cip1 , p16 INK4A /CDKN2A, and p27 Kip1 /CDKN1B (43). Sarcomas, derived from mesenchymal cells, as well as mesenchymal stem cells also display TWIST1 regulation of p21 Cip1 by both p53-dependent and -independent mechanisms (44-46). The inability of overexpressed TWIST1 to abrogate p21 Cip1 up-regulation as a result of FOXD3 expression in A375 cells may be associated with the high p53 steady state levels in these cells (Supplementary Figure S2B).…”
Section: Discussionmentioning
confidence: 99%